2004
DOI: 10.1103/physreve.69.057301
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of active versus passive advections in magnetohydrodynamic turbulence

Abstract: Active turbulent advection is considered in the context of magneto-hydrodynamics. In this case, an auxiliary passive field bears no apparent connection to the active field. The scaling properties of the two fields are different. In the framework of a shell model, we show that the two-point structure function of the passive field has a unique zero mode, characterizing the scaling of this field only. In other words, the existence of statistical invariants for the decaying passive field carries no information on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For magnetohydrodynamics, Celani et al [10,12] showed that a passive scalar displays a direct cascade towards the small scales while the active magnetic potential builds up large-scale structures in an inverse cascade process. Gilbert and Mitra [14] further found that active and passive fields have different scaling properties in the framework of a shell model. Ching et al [13] argued that such different scaling behaviors are due to the fact that the active equations possess additional conservation laws and the zero modes of the passive problem is not the leading factor that dominates the structure functions of the active field.…”
Section: Introductionmentioning
confidence: 99%
“…For magnetohydrodynamics, Celani et al [10,12] showed that a passive scalar displays a direct cascade towards the small scales while the active magnetic potential builds up large-scale structures in an inverse cascade process. Gilbert and Mitra [14] further found that active and passive fields have different scaling properties in the framework of a shell model. Ching et al [13] argued that such different scaling behaviors are due to the fact that the active equations possess additional conservation laws and the zero modes of the passive problem is not the leading factor that dominates the structure functions of the active field.…”
Section: Introductionmentioning
confidence: 99%